A Development Model Of An Illustration Design For A Story Book Titled ‘Temi’s Story’ As An Introduction Media To A Healthy Life - Aliza Shafira Nur Dhaahiru; Rusmyadi .; Muhammad Yusri Bachtiar (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2021)
The introduction of a healthy life was a habit that needed to be considered by every individual. Therefore, it was necessary to introduce early so that the habit of a healthy lifestyle can be a good habit attached to each individual. This study aimed to: (a) produce a picture book as a healthy life recognition media, (b) know the feasibility of the storybook as a healthy life introduction media, (c) know the effectiveness of pictorial story books as a healthy life-to-life recognition media. This type of research was research and development (R D) by adapting the Borg and Gall model. Stages of development included five stages: needs analysis, planning, initial product development, limited testing, and revised product test results. Needs analysis was carried out in this study to found out what the storybook was illustrated as a healthy life-to-life introduction media needed. Seven respondents responded that it was very necessary with a percentage of 100%. The story book titled "Temi’s Story" was tested on its validation and effectiveness. The results of validation by media experts were 100% very good. The results of the effectiveness test were obtained 75% feasible and 25% very feasible.